APLIKASI PENDETEKSI DINI KECANDUAN PENGGUNAAN SMARTPHONE TERHADAP PRODUKTIVITAS KERJA MENGGUNAKAN LOGIKA FUZZY - Alvendo Wahyu Aranski (JURNAL ILMIAH INFORMATIKA, 2018)
The development of smartphones at this time is very rapid. Within 1 year the bias appeared various kinds and models. The growing technology, especially smartphones, has an impact on work productivity. In one day, people can access their smartphonenya about 15-50 times. This results in decreased work productivity. With the help of fuzzy logic and applied into the app, the bias detects a quick addiction to smartphone usage. Personnel of a company, can use this application so that the productivity of employees work can be known as early as possible. From the existing calculations, obtained results that addiction to the use of smartphones affect the productivity of work as much as 80 in accordance with the existing numbers on matlab calculations. This 80 figure shows a very large part of his addiction to smartphone usage.